A high performance metal material and its preparation process
By oxidizing the carbon nanotubes and the modification of the duoline triaxyxyxyxane, the problem of poor ductility of carbon nano tubes in Al-CU-Mg aluminum alloy, realizing the high intensity and strength of the material and the material High ductility simplifies the craftsmanship and reduces the cost.
Patent Information
- Application Number
- CN202411564349.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The addition of carbon nanotubes to existing Al-Cu-Mg aluminum alloys can easily lead to agglomeration and lead to poor ductility of the material.
By oxidizing the carbon nanotubes and the modification of duoline triaxyxyxyxane, the surface of the carbon nanotuba has a hydroxyl and carboxyl group, and forming a network structure of delivery to enhance its combination with the interface of the metal material, reducing Van Dehuali , Improve decentralization.
It significantly improves the ductility and intensity of metal materials, avoids the decline in performance caused by carbon nanotimal pipe agglomeration, and simplifies the process process and reduces costs.
Smart Images

Figure CN119061285B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal material production, and in particular to a high-performance metal material and a preparation process thereof. Background Art
[0002] Al-Cu-Mg aluminum alloys have comprehensive properties such as low density, high strength, good casting performance, welding performance and processing performance. Its annealed and aged sheets are widely used in the aviation industry and civil industry, especially in the aviation industry. It plays a very important role and is one of the main structural materials in the aviation industry. After the 1980s, with the rapid development of the aerospace field, the requirements for aircraft have become higher and higher, and its service environment has become more severe. In addition to the basic high strength requirements, it must also meet the requirements of high ductility.
[0003] The specific surface area of carbon nanotubes can reach up to 1300 m 2 / g; Young's modulus is close to 1 TPa. Adding a small amount of carbon nanotubes to common aluminum alloy materials can help increase the mechanical properties of aluminum alloys such as Young's modulus and tensile strength.
[0004] For example, CN108504915B discloses an Al-Cu-Mg alloy and process with high-strength Goss+P texture and excellent fatigue resistance, wherein the alloy includes Cu 4.2-4.5%, Mg 1.2-1.5%, Mn 0.3-0.8%, Ti 0.03-0.1%, Fe<0.06%, Si<0.06%; and the Cu / Mg mass ratio is 2.9-3.7. The hot working method is to homogenize the Al Cu Mg ingot, perform high-temperature rapid hot rolling, recrystallization annealing, solution quenching, and natural aging.
[0005] However, the carbon nanotubes in the above patents are easy to agglomerate, which may easily lead to stress concentration or poor interface bonding, resulting in poor ductility of the aluminum alloy. In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem in the prior art that carbon nanotubes are easy to agglomerate, resulting in poor ductility of the alloy, and to propose a high-performance metal material and its preparation process.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The first aspect of the present application provides a process for preparing a high-performance metal material, comprising the following steps:
[0009] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, stirring evenly to obtain a dispersion, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid for a primary reaction, then adding the dispersion for a secondary reaction, then adding silicon carbide powder for a tertiary reaction, filtering and drying to obtain modified carbon nanotubes;
[0010] S2, under inert gas, the modified carbon nanotubes and pure aluminum powder are mixed, ball milled once to obtain modified carbon nanotube / aluminum powder, then the modified carbon nanotube / aluminum powder and copper powder are mixed, ball milled twice to obtain modified carbon nanotube / aluminum / copper powder, then the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D are mixed, ball milled three times to obtain modified carbon nanotube / aluminum / copper / magnesium alloy powder;
[0011] S3, cold pressing, sintering and aging the modified carbon nanotube / aluminum / copper / magnesium alloy powder to obtain a high-performance metal material.
[0012] Preferably, in step S1, the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1).
[0013] Preferably, in step S1, the ratio of the carbon nanotubes, nitric acid, sulfuric acid and silicon carbide is 1 g: (50-100) ml: (150-300) ml: (0.5-1) g.
[0014] Preferably, in step S1, the first reaction step is to stir the reaction at 80-120°C for 4-8h, the second reaction step is to reflux at 100-150°C for 1-3h, and the third reaction step is to stir at 150r / min-300r / min for 30-60min.
[0015] Preferably, in step S2, the inert gas is argon.
[0016] Preferably, in step S2, the mass ratio of modified carbon nanotubes, aluminum, copper and magnesium in the modified carbon nanotube / aluminum / copper / magnesium alloy powder is (1-3):1(4-5):(1-3).
[0017] Preferably, in step S2, the specific conditions of the first ball milling are: 200-400 r / min ball milling for 3-6 hours;
[0018] The specific conditions of the secondary ball milling are: 200-400r / min ball milling for 1-3h;
[0019] The specific conditions of the three ball millings are: 200-400r / min ball milling for 0.5-1h.
[0020] Preferably, in step S3, the specific conditions of the cold pressing are:
[0021] Cold press at 2-6Mpa for 10-20min.
[0022] Preferably, in step S3, the specific conditions for sintering are:
[0023] Sinter in a spark plasma sintering furnace at 500-700°C for 0.5-2h.
[0024] Preferably, in step S3, the specific conditions of the aging are:
[0025] Keep in an aging oven at 150-400°C for 4-8 hours.
[0026] A second aspect of the present invention provides a metal material obtained by the above-mentioned preparation process of the high-performance metal material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] Compared with the prior art, the present invention firstly performs an oxidation treatment on the carbon nanotubes, and the carbon nanotubes are acidified by the action of sulfuric acid and nitric acid, and the hydroxyl and carboxyl groups on the outer surface of the carbon nanotubes begin to appear and are conducive to modification, and the relevant impurities of the carbon nanotubes are removed, and the structure of the carbon nanotubes themselves will not be changed. On the other hand, by modifying the carbon nanotubes by dodecyltriethoxysilane, the hydroxyl groups on the surface of the carbon nanotubes react with the silane for modification, and the hydrolysis and condensation of the silane groups will produce a cross-linked network structure, which is conducive to the interface bonding between the metal and the carbon nanotubes, and dodecane will produce a steric hindrance effect, which reduces the van der Waals force. The reason for the agglomeration of carbon nanotubes is that the van der Waals force is large. The steric hindrance effect of dodecane is used to reduce the van der Waals force, which naturally enhances the dispersibility of the modified carbon nanotubes. Furthermore, the hydrogen bonding effect generated by the large number of hydroxyl and carboxyl groups on the surface of the carbon nanotubes is used to make the carbon nanotubes absorb silicon carbide. The cross-linked network structure produced by silane also strengthens the adsorption of carbon nanotubes and silicon carbide. This is mainly due to the fact that the cross-linked network structure forms more pores and channels, thereby increasing the specific surface area of the carbon nanotube surface. A larger specific surface area means that the material can contact more silicon carbide, thereby improving the adsorption effect. The cross-linked network structure makes the silicon carbide and carbon nanotubes form a stronger interaction force, thereby improving the stability of the interface between carbon nanotubes and silicon carbide. The grid-like structure also has an extrusion effect on the carbon nanotubes, thereby improving the mechanical properties of the stability of adsorption. Therefore, the chemical action of dodecane and the physical and chemical action produced by adsorption synergistically greatly improve the dispersion of carbon nanotubes, thereby enhancing the ductility of the alloy. At the same time, carbon nanotubes enhance the strength of the alloy through grain refinement, dislocation strengthening (thermal mismatch), Orowan cycle and load transfer. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0032] For simplicity, the present application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise stated, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above", "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0034] Example 1
[0035] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0036] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to adsorb the carbon nanotubes on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0037] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0038] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0039] Example 2
[0040] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0041] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:1:1:1, stirring evenly to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 100ml of sulfuric acid and 300ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0042] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0043] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0044] Example 3
[0045] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0046] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 100°C for 3h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0047] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0048] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0049] Example 4
[0050] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0051] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0052] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 200 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 400 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, then added 0.5 g silicon carbide powder and stirred at 200 r / min for 30 min to allow the carbon nanotubes to adsorb on the silicon carbide surface, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0053] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0054] Example 5
[0055] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0056] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0057] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 2:1:4.5:1.8.
[0058] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0059] Example 6
[0060] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0061] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0062] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, and ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, and ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, and ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 3:1:4.5:1.8.
[0063] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0064] Example 7
[0065] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0066] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0067] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, and ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, and ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, and ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:5:3.
[0068] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0069] Example 8
[0070] Reference Figure 1 , this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0071] S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and refluxing at 120°C for 1h, then adding 0.5g of silicon carbide powder and stirring at 200r / min for 30min to allow the carbon nanotubes to be adsorbed on the surface of silicon carbide, filtering and drying to obtain modified carbon nanotubes;
[0072] S2, mixing modified carbon nanotubes and pure aluminum powder under argon, ball milling at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixing the modified carbon nanotube / aluminum powder and copper powder, ball milling at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixing the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball milling at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlling the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4:1.
[0073] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0074] Comparative Example 1
[0075] Reference Figure 1, this embodiment provides a preparation process of a high-performance metal material, comprising the following steps:
[0076] S1, adding dodecyl triethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyl triethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring evenly to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid, stirring and reacting at 100° C. for 6 h, then adding the dispersion, refluxing at 120° C. for 1 h, filtering and drying to obtain modified carbon nanotubes
[0077] S2, mixed the modified carbon nanotubes and pure aluminum powder under argon, ball-milled at 300 r / min for 4 h to obtain modified carbon nanotube / aluminum powder, then mixed the modified carbon nanotube / aluminum powder and copper powder, ball-milled at 300 r / min for 2 h to obtain modified carbon nanotube / aluminum / copper powder, then mixed the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball-milled at 300 r / min for 0.5 h to obtain modified carbon nanotube / aluminum / copper / magnesium powder, and controlled the mass ratio of modified carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0078] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0079] Comparative Example 2
[0080] This comparative example provides a preparation process of a high-performance metal material, comprising the following steps:
[0081] S1, aluminum powder and copper powder were mixed under argon, and ball-milled at 300 r / min for 2 h to obtain aluminum / copper powder. Then, the aluminum / copper powder and magnesium alloy AZ91D were mixed, and ball-milled at 300 r / min for 0.5 h to obtain aluminum / copper / magnesium powder, and the mass ratio of aluminum, copper and magnesium was controlled to be 1:4.5:1.8.
[0082] S3, the modified carbon nanotube / aluminum / copper / magnesium powder is cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0083] Comparative Example 3
[0084] This comparative example provides a preparation process of a high-performance metal material, comprising the following steps:
[0085] S1, mix carbon nanotubes and pure aluminum powder under argon, ball mill at 300 r / min for 4 h to obtain carbon nanotube / aluminum powder, then mix the carbon nanotube / aluminum powder and copper powder, ball mill at 300 r / min for 2 h to obtain carbon nanotube / aluminum / copper powder, then mix the carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D, ball mill at 300 r / min for 0.5 h to obtain carbon nanotube / aluminum / copper / magnesium powder, and control the mass ratio of carbon nanotubes, aluminum, copper, and magnesium to be 1:1:4.5:1.8.
[0086] S3, the carbon nanotube / aluminum / copper / magnesium powder was cold pressed at 4 MPa for 15 min, then sintered at 600°C for 1 h in a spark plasma sintering furnace, and after natural cooling, kept at 200°C for 6 h in an aging furnace to obtain a high-performance metal material.
[0087] The metal materials obtained in Examples 1 to 8 and Comparative Examples 1 and 2 were die-cast into standard test bars for testing and mechanically tested on a tensile testing machine in accordance with GB / T 228.1-2021. The obtained performance parameters are detailed in Table 1 below.
[0088] Table 1 Mechanical properties of metal materials in the examples and comparative examples
[0089]
[0090] As can be seen from the above table, the present invention creatively utilizes modified carbon nanotubes to greatly enhance the mechanical properties and ductility of metal materials, avoids the deterioration of aluminum alloy ductility caused by agglomeration of carbon nanotubes in metal materials, and utilizes the cross-linked network structure produced by the hydrolysis and condensation of silane groups to facilitate the interface bonding between carbon nanotubes and metal materials. Furthermore, the hydrogen bonds generated by the hydroxyl and carboxyl functional groups on the surface of carbon nanotubes are utilized to achieve a pre-dispersion effect of carbon nanotubes in silicon carbide. The preparation process is simple and the cost is low, and it is expected to be widely used in related structural parts in the aviation industry and civil industry.
[0091] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A process for preparing a high-performance metal material, characterized in that: The following steps are involved: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, stirring evenly to obtain a dispersion, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid for a primary reaction, then adding the dispersion for a secondary reaction, then adding silicon carbide powder for a tertiary reaction, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and pure aluminum powder are mixed, ball milled once to obtain modified carbon nanotube / aluminum powder, then the modified carbon nanotube / aluminum powder and copper powder are mixed, ball milled twice to obtain modified carbon nanotube / aluminum / copper powder, then the modified carbon nanotube / aluminum / copper powder and magnesium alloy AZ91D are mixed, ball milled three times to obtain modified carbon nanotube / aluminum / copper / magnesium alloy AZ91D powder; The mass ratio of the modified carbon nanotubes, aluminum, copper and magnesium alloy AZ91D in the modified carbon nanotube / aluminum / copper / magnesium alloy AZ91D powder is (1-3):1(4-5):(1-3); S3, cold pressing, sintering and aging the modified carbon nanotube / aluminum / copper / magnesium alloy AZ91D powder to obtain a high-performance metal material.
2. A process for preparing a high-performance metal material according to claim 1, characterized in that: In step S1, the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1).
3. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S1, the ratio of the carbon nanotubes, nitric acid, sulfuric acid, and silicon carbide is 1 g: (50-100) ml: (150-300) ml: (0.5-1) g.
4. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S1, the first reaction step is to stir the reaction at 80-120°C for 4-8h, the second reaction step is to reflux at 100-150°C for 1-3h, and the third reaction step is to stir at 150r / min-300r / min for 30-60min.
5. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S2, the inert gas is argon.
6. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S2, the specific conditions of the first ball milling are: 200-400 r / min ball milling for 3-6 hours; The specific conditions of the secondary ball milling are: 200-400r / min ball milling for 1-3h; The specific conditions of the three ball millings are: 200-400r / min ball milling for 0.5-1h.
7. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S3, the specific conditions of the cold pressing are: Cold press at 2-6Mpa for 10-20min.
8. The process for preparing a high-performance metal material according to claim 1, characterized in that: In step S3, the specific conditions of the sintering are: sintering at 500-700° C. for 0.5-2 h in a spark plasma sintering furnace; the specific conditions of the aging are: keeping warm at 150-400° C. for 4-8 h in an aging furnace.
9. A metal material obtained by the preparation process of the high-performance metal material according to any one of claims 1 to 8.
Citation Information
Patent Citations
An Al-Cu-Mg alloy with high-strength Goss+P texture and excellent fatigue resistance, and its processing method.
CN108504915B
Preparation method for carbon nano-tube aluminum matrix composite material
CN106756274A
Preparation method of multi-dimensional carbon material composite reinforced copper-based material
CN113278838A